Adoption of software development life cycle (SDLC) model in games development framework for serious games applications - Siti Normaziah, Ihsan; Tuty Asmawaty, Abdul Kadir (American Scientific Publisher, 2018)
Fulfilling the client’s requirement within the given budget and timeframe in the developments of software projects is the measurement of the successful of the project. It must follow the standards process in a software engineering model. Each phase in the software process model led to the expert team to manage the process of developing the software which include the requirements, usability, time management and costing of the project. The standards will assist in supervising and managing the development process. Nowadays, serious games are getting to be outstandingly in many fields such as military, healthcare, management, tourism, education and others. The motivation of learning using the serious games is not limited to enjoying the games, but it’s help the player getting knowledge and experiential in practicing the learning. The aim isn’t simply playing for pure entertainment, yet share the knowledge, giving the training and experience the skills. Looking to the increasing numbers of serious games in many industries, the flow, process and usability principles must be design in a systematic way to map with the software engineering activities. Overall aims in this paper propose a framework model for serious games adopting from Software Development Life Cycle (SDLC). It is targeted to help examining this field and implement the software processes that serve development team to identify the distinctive necessity of the software.